(untitled) (Advancements in Homeopathic Research, 2024)
Mastitis is characterized by inflammation in the breast, which may or may not be associated with an infection. While it typically occurs in women of childbearing age, it can manifest in individuals of all age groups, including males. In this case report we present a case of chronic mastitis, presenting with complaints of severe pain in left breast with inflammation and pus formation present on lateral side. Pain aggravated on motion and touch. After complete case taking and proper repertorisation than on the basis of totality of symptoms Phytolacca decandra 200 was prescribed.